2016
DOI: 10.1063/1.4945703
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the zinc-oxygen divacancy in ZnO crystals

Abstract: An electron paramagnetic resonance (EPR) spectrum in neutron-irradiated ZnO crystals is assigned to the zinc-oxygen divacancy. These divacancies are observed in the bulk of both hydrothermally grown and seeded-chemical-vapor-transport-grown crystals after irradiations with fast neutrons. Neutral nonparamagnetic complexes consisting of adjacent zinc and oxygen vacancies are formed during the irradiation. Subsequent illumination below ∼150 K with 442 nm laser light converts these (VZn2− − VO2+)0 defects to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…The divacancy can nominally exist in two different configurations, axial (aligned along the [0001] direction) or azimuthal (lying in the basal plane). Holston et al 17 have assigned an EPR signal to the azimuthal configuration of the divacancy only, and our calculations indicate that this configuration is more stable, although the difference in energy is small. For this reason, we present results for the azimuthal configuration only.…”
Section: B Divacancysupporting
confidence: 47%
See 1 more Smart Citation
“…The divacancy can nominally exist in two different configurations, axial (aligned along the [0001] direction) or azimuthal (lying in the basal plane). Holston et al 17 have assigned an EPR signal to the azimuthal configuration of the divacancy only, and our calculations indicate that this configuration is more stable, although the difference in energy is small. For this reason, we present results for the azimuthal configuration only.…”
Section: B Divacancysupporting
confidence: 47%
“…Several recent experimental studies highlight the closeassociate V Zn V O pair, hereby referred to as the divacancy, as another important defect in ZnO, especially in processed samples, e.g., after irradiation, annealing or polishing [15][16][17] . In contrast to its isolated constituents, however, first-principles calculations on the divacancy are scarcely available in the literature 16,[18][19][20][21][22] , and predominantly based on semilocal functionals.…”
Section: Introductionmentioning
confidence: 99%
“…Since V Zn are more mobile than V O , 32 they can migrate to the surface during the TT and reach the V O to form the divacancy. 33,34 This complex acts as a recombination center that fades out the photoresponse of the samples as its concentration increases. Then, for low q d the quantity of V O , introduced by the TT, overpasses the number of preexistent V Zn , relatively low concentration of complexes is formed, and the PC increases due to the new traps generated.…”
Section: Resultsmentioning
confidence: 99%
“…Divacancies are also likely be introduced by H-or He implantation. For example, Holston et al [16] observed an EPR signal in neutron-irradiated ZnO, which they assigned to the Zn-O divacancy. Moreover, both isolated and hydrogenated divacancies have been identified in H-implanted silicon [17].…”
Section: Introductionmentioning
confidence: 99%